The changes in soil-biological processes and structure of microbial community of agrochernozems in conditions of different ways of soil cultivation - O. V. Kutovaya; A. M. Grebennikov; A. K. Tkhakakhova; V. A. Isaev; V. M. Garmashov; V. A. Bespalov; Yu. I. Cheverdin; V. P. Belobrov (Бюллетень Почвенного института им. В.В. Докучаева)
The impact of soil cultivation methods (tillage with soil overturning at a depth of 20-22 and 14-16 cm, beardless plowing and surface treatment respectively at a depth of 14-16 and 6-8 cm, and also zero or minimal tillage)) on biological activity of various ecology-trophic groups of microorganisms on agronochernozems of the Kamennaya Steppe (Voronezh oblast) using classical inoculation methods on elective media. It is shown that chernozems are highly resistant soils that are resistant to external impacts, preserving high biological activity even at the maximum mechanical treatment. Tillage with soil overturn leads to aeration of the arable horizon and the activity initiation of aerobic microorganisms of the carbon cycle, responsible for the mineralization of both complex and simple organic compounds of the soil. The contribution of microorganisms of the nitrogen cycle (nitrate-reducers and nitrogen fixers) to the overall biological activity of migratory-micellar chernozems of arable land and layland was minimal. The level of mechanical impact on the soil affects the quantitative indices and biological activity of microorganisms in the soil - the stronger the effect, the deeper layers are affected. The processes of entrance for fresh organic matter prevail over the processes of mineralization practically in all variants of the experiment, except for tillage with the soil overturn to a depth of 14-16 cm, as indicated by the values of the mineralization coefficients. The strongest humus-accumulative effect was observed in the variant with zero treatment, which is maximally approximated to such processes, occurred in a layland. Minimal soil cultivation will help to preserve the unique structure of chernozem soil, to increase the flow of fresh organic remains, to preserve the high biological diversity which is specific for natural biocenosises.